Pemanfaatan Media Augmented Reality dalam Keterampilan Berbicara Siswa Kelas VII SMPN 1 Galis Pamekasan - Novi Maulidia; Agik Nur Efendi; Mochamad Arifin Alatas; Aldi Firnanda (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The development of digital technology encourages the education sector to use interactive and contextual learning methods. One of the emerging innovations is the use of Augmented Reality (AR) media, which can combine the real world and the online world to support students' understanding in a more concrete and engaging manner. The purpose of this research is to implement media innovation based on Augmented Reality. The results of the use in speaking skills and student responses in learning. In this study, a qualitative descriptive method was used. Data collection techniques included direct observation, interviews, and documentation conducted on seventh-grade students at SMPN 1 Galis as research subjects. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion drawing. This research proves that Augmented Reality (AR) media can actively encourage the involvement of seventh-grade students at SMPN 1 Galis and enhance their confidence in speaking. The display of three-dimensional objects through AR makes it easier for students to understand the material and construct sentences more clearly and structured. The use of Augmented Reality (AR) media in speaking skills learning helps students' understanding, encourages their engagement in the learning process, and fosters confidence when speaking.Perkembangan teknologi digital mendorong dunia pendidikan untuk menggunakan metode pembelajaran yang interaktif dan kontekstual. Salah satu inovasi yang muncul adalah penggunaan media Augmented Reality (AR) yang mampu menggabungkan dunia nyata dan daring untuk mendukung pemahaman siswa secara lebih konkret dan menarik. Tujuan penelitian ini melaksanakan inovasi media berbasis Augmented Reality. Hasil penggunaan dalam keterampilan berbicara, dan respon siswa dalam pembelajaran. Pada penelitian ini menggunakan metode deskriptif kualitatif. Teknik pengumpulan data berupa observasi langsung, wawancara, dan dokumentasi yang dilakukan terhadap siswa kelas VII SMPN 1 Galis sebagai subjek penelitian. Analisis data dilakukan melalui tiga tahap, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini membuktikan bahwa media Augmented Reality (AR) mampu mendorong keterlibatan siswa kelas VII SMPN 1 Galis secara aktif serta meningkatkan rasa percaya diri mereka dalam berbicara. Tampilan objek tiga dimensi melalui AR mempermudah siswa dalam memahami materi dan menyusun kalimat dengan lebih jelas dan terstruktur. Penggunaan media Augmented Reality (AR) dalam pembelajaran keterampilan berbicara membantu pemahaman siswa, mendorong keterlibatan mereka dalam proses belajar, serta menumbuhkan rasa percaya diri saat berbicara.